2023
DOI: 10.1111/1750-3841.16471
|View full text |Cite
|
Sign up to set email alerts
|

Health versus environmental benefits: Does additional information influence consumer acceptance of pulse‐based spreads?

Abstract: Despite the known health benefits and the potential for substituting less environmentally sustainable consumed foods such as meat, the current intake of pulses in developed countries remains less than recommended. Barriers are related to sensory characteristics and lack of knowledge about preparation, while drivers of environmental benefits are intangible. The aim of this study was to investigate the effect of additional information about health or environmental benefits of pulses on the acceptance of novel pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Studies into how additional information influences consumer preferences for pulses and pulse-based products agree that when consumers are informed of positive health or environmental impact this increases their intention to consume the product (Röös et al 2020). Some studies find that positive health outcomes are a stronger motivation for eating less meat compared with environmental reasons (Tobler et al 2011) and others identified that when consumers were informed of both environmental and health benefits this further increased their intention to consume the product (Henn et al 2023). Positive messaging about the environmental (including net zero) and health benefits of pulse consumption should therefore be focused and strengthened by government messaging, food research and industry advertising and branding to align consumer intentions more closely with consumer decisions.…”
Section: Consumingmentioning
confidence: 99%
“…Studies into how additional information influences consumer preferences for pulses and pulse-based products agree that when consumers are informed of positive health or environmental impact this increases their intention to consume the product (Röös et al 2020). Some studies find that positive health outcomes are a stronger motivation for eating less meat compared with environmental reasons (Tobler et al 2011) and others identified that when consumers were informed of both environmental and health benefits this further increased their intention to consume the product (Henn et al 2023). Positive messaging about the environmental (including net zero) and health benefits of pulse consumption should therefore be focused and strengthened by government messaging, food research and industry advertising and branding to align consumer intentions more closely with consumer decisions.…”
Section: Consumingmentioning
confidence: 99%